THE MATHEMATICS LEARNING MODEL’S FOR EARLY GRADE STUDENTS: CONTEXTUAL OR PROBLEM-BASED LEARNING - Moh. Farizqo Irvan; Mohammad Adam Jerusalem; Habibullah Habibullah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2020)
This research aimed to know the appropriate learning model was applied in early grade mathematics learning by showed the differences in mathematics learning outcomes of students who use contextual teaching-learning and problem-based learning. This research method was quasi-experiment with a posttest only control group design. The population of this research were 3rd grade students of SD Negeri Wonosari, Semarang City. The sampling technique was used to cluster random sampling with two experimental classes. The first experimental class used contextual teaching-learning and the second experimental class used problem-based learning. The data were analyzed using a one-way ANOVA test.  The results showed that there were differences between student mathematics learning outcomes in three classes. Student learning outcomes that applied contextual teaching and learning were better than mathematics learning outcomes of students who applied problem-based learning or conventional learning because contextual teaching and learning more emphasis on meaningful learning from real life that made it easier for students to understand. The teacher should be able to choose the appropriate model to be applied in mathematics learning following the grade level so that mathematics learning in the early grade could run optimally. So, this model was suitable to apply in early grade mathematics learning.